EFFECT OF AL HUWAYZA MARSH BOUNDARY CONFIGURATION ON THE VELOCITY PATTERNS AND WATER QUALITY DISTRIBUTION (Journal of Engineering, 2009)
A two-dimensional depth-averaged hydrodynamic model and a two-dimensional waterquality parameters transport model were developed to simulate the characteristics of AlHuwayza Marsh, which is considered the largest and most important marsh in the south ofIraq. The hydrodynamic model for Al Huwayza Marsh was built by using RMA2 model,while the water quality model was built by using RMA4 model. These two models are part ofSurface Water Modeling System, SMS, software package.To investigate the effect of the marsh boundary configuration on the variation of thevelocity pattern and the water quality within the marsh, both of the hydrodynamic and thewater quality models were applied to three cases of boundary configuration of Al HuwayzaMarsh. The first case represents the natural extension of the marsh boundary. The second caserepresents the existing boundary configuration of the marsh, in which the south west of themarsh is bounded by a dyke. The third case represents the Iraqi part of the marsh bounded bythe south west dyke and a dyke along the Iraq-Iranian borders, which when completed willseparate the marsh into two parts.Models runs were based on above cases of Al Huwayza Marsh boundary configurationand topographical survey, hydrological measurements and routing, and water qualitymeasurements carried out by the Center of Rehabilitation of Iraqi Marshlands. Discharges ofall feeders and stages of the outlets are considered for wet, normal, and dry years. Feeder’sseasonal discharges were averaged. High and low concentrations of three selected waterquality parameters of the marsh feeders were adopted in the model runs.Generally, it was found that the flow velocities are relatively high at the inlets andoutlets of the marsh. The construction of the dyke along the Iraqi-Iranian border leads tovariation in the direction of water flow in all portions of the marsh and a great reduction inAsSuwayb River discharge. While, a slight effect was noticed in the mixing process of thefeeders’ water of different concentration in case three compared to other cases